Adventure-based cruise tourism and emergency response -training for increased polar-water emergency management competence - Sætren, Gunhild Birgitte; Stenhammer, Hege Christin; Andreassen, Natalia; Borch, Odd Jarl (2021)
Poster presentation at the Svalbard Science Conference SSC21, 02.11.21 - 03.11.21, Oslo, Norway, arranged by Forskningsrådet. https://www.forskningsradet.no/en/svalbard-science-forum/ssf-tools-and-funding-schemes/svalbard-science-conference/ . Nature-based tourism has increased significantly in recent years. The special segment adventure travel has doubled in size, from 10 to 20 percent of the international tourism market. This type of tourism is characterized by visiting remote and spectacular areas, and uniqueness. One of the most popular type of adventure based travel is so-called expedition cruise. The number of cruise vessels is increasing and a significant numbers of new vessels are contracted. This includes the number of cruise vessels visiting the High North and Svalbard. The polar regions are characterized by challenging weather, cold climate, a lack of infrastructure and equipment as well as a vulnerable environment. The polar regions are also political sensitive areas. Accidents in this area demand fast response from the responsible government. This is why there has to be constant focus on risk reducing efforts including both increased safety and preparedness and reduction of consequences if and accident should happen. Polar water competence is a very important factor for safe operation and an efficient emergency response. This paper highlights how personnel from both cruise vessels and the emergency response agencies can train to meet risks of life and environment in the case of cruise ship accidents with the need for mass evacuation. The paper builds upon the experience from computer-assisted exercises (CAX) of key crisis management personnel. This included the use of simulator training at NORDLAB the Nord university emergency management laboratory. New concept for management and cross-agency cooperation was included. The exercise included mentors from the emergency response agencies and students with background from companies, the government emergency response agencies. The findings reveal the ...